Dual layer computed tomography: Reduction of metal artefacts from posterior spinal fusion using virtual monoenergetic imaging. Issue 105 (August 2018) - Dangelmaier, Julia; Schwaiger, Benedikt J.; Gersing, Alexandra S.; Kopp, Felix F.; Sauter, Andreas; Renz, Martin; Riederer, Isabelle; Braren, Rickmer; Pfeiffer, Daniela; Fingerle, Alexander; Rummeny, Ernst J.; Noël, Peter B.
Highlights: VMI effectively reduces metal artefacts caused by posterior spinal fusion. DLCT allows a retrospective evaluation of VMI obtained at 120 or 140 kVp whenever required. This work provides dedicated keV-settings to evaluate anatomical areas of peculiar interest following posterior spinal fusion. Abstract: Introduction: To evaluate the clinical potential of dual layer computed tomography (DLCT) for posterior fusions of the thoracic and lumbar spine and determine the optimal keV-settings for an improved overall image quality and effective reduction of metal artefacts affecting the implant inheriting vertebral body, the spinal canal, the paravertebral muscle and aorta. Methods and materials: Twenty patients with posterior thoracic and lumbar spinal fusion, who underwent a 120kVp- DLCT scan were included in this study. Two independent readers evaluated axial 0.9 mm slides with soft tissue and bone window settings. Image quality of the conventional scan was compared to virtual monoenergetic images (VMI) at 40, 60, 80, 100, 120, 140, 160, 180 and 200 keV. Diagnostic image quality was assessed on a four point Likert-scale overall, as well as specifically for the implant inheriting bone, paravertebral muscle, spinal canal or aorta. The Hounsfield Units (HU) of the area with the most pronounced streak artefact as well as HU of a reference area containing fat and muscle were documented for each keV-setting and compared to the conventional image. SNR and CNR were calculated for each of the four anatomic areas. Statistical analysis was conducted for the total collective and separately for the thoracic and lumbar spine level. Results: Starting from 80 keV qualitative analysis revealed significant improvement of overall image quality and benefit for each tissue separately compared to the conventional images (CI) (p-values in the range from <0.001 to 0.005). 180 keV was considered the optimal monoenergetic setting regarding the overall image quality. For the assessment of the implant inheriting bone, the spinal canal, paravertebral muscle and aorta 200, 180, 160 and 180 keV were rated to be the most sufficient. Our results reveal high inter-reader agreement for qualitative evaluations (intra-class correlation coefficients >0.927; p < 0.05). HU values within the most pronounced streak artefact increased significantly with higher keV (p < 0.001), while there was no significant alteration of HU within the reference area. A decrease in SNR and CNR for higher VMI was revealed by our results. Conclusion: VMIs of higher energies provide significant reduction of metallic artefacts from posterior spinal fusions. Dedicated keV settings to evaluate either the implant inheriting bone, the spinal canal, adjacent muscle or aorta – structures, which are frequently of particular interest after posterior spinal fusion – are recommended. In addition, an optimal keV for an improved overall image quality is proposed.